2018
DOI: 10.1111/adb.12640
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala volume is associated with risky probability cognition in gambling disorder

Abstract: Gambling disorder (GD) is characterized by continual gambling despite negative consequences. Risky decision-making is a hallmark of the disorder. We applied a tool from behavioral economics for assessing probability cognition in both gain and loss domains to GD. We aimed to examine the alteration of probability cognition and its relationship with brain structure in GD. Forty-six GD patients and 52 age-matched healthy controls (HCs) conducted a risky choice task in which subjects should choose between a sure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The insular cortex has also been shown to mediate decision making during the rGT (Ishii et al, 2015; Pushparaj et al, 2015; Daniel et al, 2017). These data complement studies in humans demonstrating that various regions of the PFC are recruited during the IGT (Fellows and Farah, 2005; Tanabe et al, 2007; Lawrence et al, 2009; Power et al, 2012), and the amygdala mediates GD in humans (Bechara et al, 1999; Takeuchi et al, 2019).…”
Section: Additional Models Of Behavioral Addictionssupporting
confidence: 77%
“…The insular cortex has also been shown to mediate decision making during the rGT (Ishii et al, 2015; Pushparaj et al, 2015; Daniel et al, 2017). These data complement studies in humans demonstrating that various regions of the PFC are recruited during the IGT (Fellows and Farah, 2005; Tanabe et al, 2007; Lawrence et al, 2009; Power et al, 2012), and the amygdala mediates GD in humans (Bechara et al, 1999; Takeuchi et al, 2019).…”
Section: Additional Models Of Behavioral Addictionssupporting
confidence: 77%
“…Changes in NAcc's structure 47 and function 22,25 related to GD have been observed in previous studies. The same is true for amygdala's structure 48 and function, 10 as well as for OFC's structure 49 and function 5 . Our study adds to these findings by considering the functions of these structures concurrently and in a network.…”
Section: Discussionsupporting
confidence: 67%
“…On the one hand, decision making deficits in addictive disorders like PG and substance use disorders are related to brain regions including the dorsolateral prefrontal cortex, the ventromedial prefrontal/orbitofrontal cortex, and the insula (32)(33)(34)(35)(36). On the other hand, PG patients showed reduced GMV in amygdala (37), putamen (38) hippocampal areas (38,39), and various prefrontal regions (40,41). However, we found no study investigating the association of decision making deficits and GMV in PG patients.…”
Section: Decision Making and Gray Matter Volume In Pgmentioning
confidence: 79%
“…Connecting to the previously discussed topic of impulsivity, Ruiz de Lara et al (41) also investigated impulsivity measures and found a negative correlation between GMV in the right ventrolateral prefrontal cortex and a self-reported impulsivity facet. Similarly, a study only exploring amygdala and striatum volumes, reported a negative correlation between left amygdala GMV and impulsivity in a PG sample (37). Additionally, findings from a healthy sample showed that cognitive impulsivity is negatively correlated to GMV in the orbitofrontal cortex (47).…”
Section: Decision Making and Gray Matter Volume In Pgmentioning
confidence: 94%